Pengaruh Kualiatas Makanan Dan Suasana Terhadap Kepuasan Konsumen Pada Pizza House Di Kota Lhokseumawe - Intan Syafriani; H Heriyana; Yusniar Yusniar (Jurnal Visioner & Strategis, 2022)
This study examined the effect of food quality and atmosphere on consumer satisfaction at Pizza House in Lhokseumawe City. This study used primary data obtained by distributing questionnaires to 115 respondents who were selected using a non-probability sampling method with purposive sampling technique. The data analysis method used was multiple linear regression with the help of SPSS 24.0.  The results  partially indicated  that  food  quality significantly influenced consumer  satisfaction  at Pizza  House in  Lhokseumawe City,  and  atmosphere significantly influenced consumer satisfaction at Pizza House in Lhokseumawe City. Simultaneously, food quality and atmosphere significantly influenced consumer satisfaction at Pizza House in Lhokseumawe City.